New Approach of Degree-based Topological Indices for Indentity Graph of Integer Modulo n - Syarifudin, Abdul Gazir; Husni, Muhammad Naoval; Santi, Laila Maya; Shaumi, Nurina Fadlila; Suwastika, Erma (Jurnal Matematika, 2025)
An identity graph of group  denoted by  is a simple graph with vertex set is elements of  and two vertices  are adjecent if and only if , with all vertices are adjecent with vertex . In this paper will discuss about some indeces based on degree for every vertix of identity graph of integer group modulo . The results of this research obtained first Zagreb index, second Zagreb index, and Gutnan index of identity graph of integer group modulo